2016
DOI: 10.1016/j.ijdevneu.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of hypothermia in inflammatory‐sensitized hypoxic‐ischemic encephalopathy

Abstract: Hypothermia is neuroprotective against inflammatory-sensitized hypoxia-ischemia possibly through a hypothermia-induced increase of antioxidant enzymes. This neuroprotective effect seems to be independent of the interleukin-1 system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…The severe injury seen in this region may be resistant to the benefits of TH in this model ( 20 , 21 ). These data are consistent with previous studies that demonstrated that TH-mediated attenuation of caspase-dependent pathway activation after HI in neonatal mice is region-specific ( 8 ) and that TH was neuroprotective in the HI-induced penumbra, but not in the core, and that protective effect was associated with a TH-induced increase of antioxidant enzymes SOD-1 and GPx, leaving several inflammatory mediators unchanged, including IL1β and MMP-9 ( 22 ). Another possibility is that the inflammatory response is strongest in the hippocampus, as evident from the Iba1 and GFAP coverage of microglia and astrocytes respectively, thus preferentially affecting oligodendrocytes in that region ( 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…The severe injury seen in this region may be resistant to the benefits of TH in this model ( 20 , 21 ). These data are consistent with previous studies that demonstrated that TH-mediated attenuation of caspase-dependent pathway activation after HI in neonatal mice is region-specific ( 8 ) and that TH was neuroprotective in the HI-induced penumbra, but not in the core, and that protective effect was associated with a TH-induced increase of antioxidant enzymes SOD-1 and GPx, leaving several inflammatory mediators unchanged, including IL1β and MMP-9 ( 22 ). Another possibility is that the inflammatory response is strongest in the hippocampus, as evident from the Iba1 and GFAP coverage of microglia and astrocytes respectively, thus preferentially affecting oligodendrocytes in that region ( 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…An in vitro study on the effect of temperature on cytokine release from microglia showed that IL-10 was down-regulated by HT; this suggests a pro- rather than anti-inflammatory effect of HT [29]. In a rat, pre-clinical model of inflammatory sensitized HIE, neuroprotection from HT was independent of the interleukin-1 system and was dependent on an increase in antioxidant enzymes [30]. Rapid rewarming (by 3 °C over 20 min) has been associated with a pro-inflammatory state in a rodent model, with a robust increase in IL-6 and IL-1β [31].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few clinical or preclinical models address this question. However, a well-established anti-inflammatory effect of HT is the down regulation of oxidative stress within the brain ( 91 , 97 , 116 118 ). It has also been reported that HT is neuroprotective by limiting apoptotic cascades in human term newborns ( 110 , 119 121 ).…”
Section: New Hypotheses Bringing New Treatmentsmentioning
confidence: 99%